Thrombo-inflammatory prognostic score can predict the outcome of stroke: a retrospective cohort study - Zhu, Xingyu; Lan, Lin; Liu, Yi; He, Na; Wu, Jie; Guo, Yingqiang; Li, Hong; Li, Dongze (Frontiers in Aging Neuroscience, 2024)
Introduction Inflammatory and thrombotic biomarkers are simple prognostic indicators of adverse clinical outcomes in patients with ischemic stroke (IS). However, isolated assessment of inflammatory or thrombus biomarkers in patients with IS is limited in clinical practice. Methods This study aimed to evaluate the predictive value of a novel, simplified thrombo-inflammatory prognostic score (TIPS) that combines both inflammatory and thrombus biomarkers in the early phase of IS and to identify high-risk patients at the time of admission. The study population comprised 915 patients with a primary diagnosis of IS in the emergency departments of five grade A tertiary hospitals in China. Results Patients were divided into two groups based on the modified Rankin Scale (mRS): <3 and ≥3. TIPS with a value of “2” indicates biomarkers for high inflammation and thrombosis, “1” represents a biomarker, and “0” signals the absence of a biomarker. Multivariate logistic regression analysis was employed to identify the association between TIPS and clinical outcomes. TIPS was an independent predictor of unfavorable functional outcomes and mortality. It had a superior predictive value for clinical outcomes compared to the National Institutes of Health Stroke Scale (NIHSS) (effect ratio, 37.5%), D-dimer (effect ratio, 12.5%), and neutrophil-to-lymphocyte ratio (effect ratio, 25%). Conclusion The survival probability of TIPS with a score of 0 is twice as high as that of TIPS with a score of 2. The survival rate for TIPS with a score of 1 is one time higher than that for TIPS with a score of 2. The predictive value of TIPS for unfavorable functional outcomes is represented by an AUC of 0.653. TIPS is associated with an increased risk of death and unfavorable functional outcomes in patients with IS and may be a useful tool for identifying high-risk patients at the time of admission.